2016
DOI: 10.1371/journal.pone.0147583
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Circadian Dysfunction in the BACHD Mouse Model of Huntington’s Disease

Abstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder that affects men and women in equal numbers, but some epidemiological studies indicate there may be sex differences in disease progression. One of the early symptoms of HD is disruptions in the circadian timing system, but it is currently unknown whether sex is a factor in these alterations. Since sex differences in HD could provide important insights to understand cellular and molecular mechanism(s) and designing early intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 87 publications
4
56
0
Order By: Relevance
“…Mouse models of HD also exhibit a progressive and rapid breakdown of the circadian rest/activity cycle that closely mimics the condition observed in human patients. Phenotype includes loss of consolidated sleep, increased wakeful activity during the rest phase, and more sleep during the active phase [153,[157][158][159]. Collectively this prior research supports the hypothesis that circadian dysfunction is an integral component of HD pathophysiology and could be contributing to the deficits in white matter.…”
Section: Huntington Disease (Hd)supporting
confidence: 59%
“…Mouse models of HD also exhibit a progressive and rapid breakdown of the circadian rest/activity cycle that closely mimics the condition observed in human patients. Phenotype includes loss of consolidated sleep, increased wakeful activity during the rest phase, and more sleep during the active phase [153,[157][158][159]. Collectively this prior research supports the hypothesis that circadian dysfunction is an integral component of HD pathophysiology and could be contributing to the deficits in white matter.…”
Section: Huntington Disease (Hd)supporting
confidence: 59%
“…We used male mice for these studies as we have previously demonstrated that there are sex differences in the circadian phenotype and SCN pathophysiology in the BACHD line (Kuljis et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Like other mouse models of HD (Loh, Kudo, Truong, Wu, & Colwell, ; Menalled et al, ; Morton et al, ), the bacterial artificial chromosome transgenic mouse model of HD (BACHD) exhibits disrupted rhythms in sleep, activity, and physiology (Kudo, Loh, et al, ; Kuljis et al, ; Schroeder et al, ). Early in the disease progression (3 month of age), mutant dorsal SCN neurons lose their daily rhythms in electrical activity (Kudo, Schroeder, et al, ; Kuljis et al, ), suggesting circadian behavioral deficits are caused by pathophysiology of the SCN. In this study, we first sought to determine whether the SCN firing rate deficits continue when GABA‐mediated synaptic transmission is blocked, and whether the daily rhythms in resting membrane potential (RMP) and conductance are disrupted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our female mice outperformed male animals in cognitive, motor, and nest tests. Studies in HD mouse models have suggested sex-associated differences in the severity or the age of onset of the HD phenotype [15,49,50], with females displaying less severe symptoms or a later development of the disease than males. These findings in mice are reminiscent of clinical observations in HD patients, where a later onset of motor HD alterations has been reported in women [64].…”
Section: Discussionmentioning
confidence: 99%
“…We then tested whether Suvorexant injections over a prolonged period of 5 days might be effective for improving behavioral performances. R6/1 female mice were also included in addition to R6/1 male mice in this study because of the importance of gender differences reported in HD [15,49,50]. Animals were administered drug for 5 consecutive days at 7:00 a.m. daily, and tested in the above behavioral tasks on the 5th day, 12 h after the last injection (7:00 p.m.).…”
Section: Experiments 4: Orx Antagonism Alleviates Behavioral Impairmenmentioning
confidence: 99%